PRE-TEACHER STUDENT WITH PROBLEMS OF HANDLING ENGLISH TEACHING PRACTICE IN MICROTEACHING CLASS ACTIVITY: MANAGING CLASSROOM INTERACTION AND APPLYING COMMUNICATIVE LANGUAGE TEACHING-BASED - Sujariati, Sujariati; AR, Nirwana; Ananda.P, Resky Aiman (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to find out the student’s problems in handling microteaching class as a pre-teacher. Through observation and interview some findings have been found data and then analyzed the data through descriptive qualitative method. In this research involved fifteen of students as the subject research who are as pre-teacher and participant who are observed and interviewed. The sample as subject research of this study are students are studying at faculty of trainer and education Universitas MUhammadiyah Makassar. The findings of this study provided and described qualitatively. The result findings of the study showed there are ten problems related to classroom management appeared on the pre-teacher when they practice microteaching. Through observation, some of the problems exactly mostly happen to other teacher generally when their teaching such as problem in implementing language use communicatively in teaching interaction, usage language function appropriately, and miss of distributing feedback and evaluation before close the teaching. Data from interviewed showed that many factors influencing the problems on them. Refers to the factors, exactly the factors mostly come from the students itself, it means that the factors are categorized in internal factors of the pre-teacher itself. In this discussion also provided the solution to solve the problems with clear description in order that is would be valuable to the next researcher or for a reader.